a) [tex]\frac{1}{2}x - 4 = x - 6[/tex] /*2
x - 8 = 2x - 12
x - 2x = -12 + 8
-x = -4
x = 4
b) [tex]x - 5 = \frac{1}{3}x + 1[/tex] /*3
3x - 15 = x + 3
3x - x = 3 + 15
2x = 18 /:2
x = 9
c) [tex]\frac{x}{4} - \frac{1}{4} = 2[/tex] /*4
x - 1 = 8
x = 8 + 1
x = 9
d) [tex]\frac{x}{5} - 3 = x + \frac{1}{5}[/tex] /*5
x - 15 = 5x + 1
x - 5x = 1 + 15
-4x = 16 /:(-4)
x = -4
e) [tex]\frac{5}{6}(x-1) = 4[/tex]
[tex]\frac{5}{6}x - \frac{5}{6} = 4[/tex] /*6
5x - 5 = 24
5x = 24 + 5
5x = 29
x = [tex]\frac{29}{5}[/tex]
x = [tex]5\frac{4}{5}[/tex]
f) [tex]-\frac{1}{2}(-x-6) = -x[/tex]
[tex]\frac{1}{2}x + 3 = -x[/tex] /*2
x + 6 = -2x
x +2x = -6
3x = -6 /:3
x = -2